Dietary management and physical exercise can improve climbing defects and mitochondrial activity in Drosophila melanogaster parkin null mutants. Issue 2 (3rd April 2018) - Bajracharya, Rijan; Ballard, J. William O.
ABSTRACT: Physical exercise can improve gait, balance, tremor, flexibility, grip strength and motor coordination in Parkinson's disease (PD) patients. Several lines of evidence have also shown the therapeutic potential of dietary management and supplementation in halting the progression of PD. However, there is a lack of research on the combined effects of physical activity and nutrition in the progression of PD. We test the effects exercise and dietary modification in a Drosophila model of PD. In this study, we fed Drosophila parkin mutants high protein and high carbohydrate diets without and with stearic acid (4 treatments in total). In parallel, we subjected mutants to a regimen of exercise using a purpose-built 'Power tower' exercise machine. We then measured climbing ability, aconitase activity, and basal mitochondrial ROS levels. We observed that exercising parkin mutants fed the high protein diet improved their climbing ability and increased aconitase activity. There was an additional improvement in climbing and aconitase activity in exercised parkin mutants fed the high protein diet supplemented with stearic acid. No benefits of exercise were seen in parkin mutants fed the high carbohydrate diet. Combined, these results suggest that dietary management along with physical activty has potential to improve mitochondrial biogenesis and delay the progression of PD in Drosophila parkin mutants.